Technical Efficiency of Palm Oil Production in West Kalimantan - Ismiasih, Ismiasih (HABITAT, 2017)
This research aims to analyze the technical efficiency and source of technical inefficiency of palm oil production. The data used are secondary data from agricultural census survey in 2013 with a sample of 1229 farmer. Technical efficiency is measured by using stochastic frontier production function and is estimated using MLE method assuming that Cobb-Doughlas is the functional form of palm oil. From the research result, it is known that the factors that influence the technical efficiency of palm oil production in West Kalimantan Province are a number of productive trees, plant age, urea fertilizer, SP36, NPK, labor and dummy pesticide.Â Furthermore, variables of the percentage of own capital, membership of cooperative and membership of contract farming are influencing to reduce technical inefficiency. Therefore, efforts to improve the technical efficiency is to increase the role of the cooperative to its members, and increase the involvement of palm oil farmers in the plasma pattern.